Impact of Machine Translation on Japanese Writing Skills - Kun Makhsusy Permatasari; Irawati Agustine (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to determine the impact of machine translation on Japanese writing skills. The ability to write Japanese is also understood through the components of writing. This study uses experimental research using a one-group experimental design. It was conducted at Private University in Jakarta. Data collection techniques are documents and written tests. The participants were 60 students who received the Writing Course. To determine the effect of using machine translation on Japanese writing skills, it was analyzed using the t-test: Paired Two Sample for Means. The results of the study concluded that machine translation had a significant impact on the completion of writing assignments so which led to an increase in writing ability. However, in the study of each component of writing, there are still weaknesses in the aspects of grammar and the development of logical ideas. Therefore, this research has implications for understanding how machine translation works, which has limitations and students must review their writings at the editing stage.